Periódicos científicos eletrônicos: reflexões sob o viés CTS - Alves, Ana Paula Meneses (2010)
Since middle of 20th Century, the effervescence of scientific, technological and economic development incites changes in the several fields of society, evidencing one necessity of a critical view, of social line, before science and technology (S&T). These views lead in outbreak of Science, Technology and Society Movement STS − that search one perception more critical for the role developed for S&T and the defense of S&T aren t disconnected of social questions. The current technological changes impact over all society and it s not different over scientific community. Appraise and reflect about impacts and reactions of community is one of study areas of STS field. Focalizing on STS field, accentuate the following topics Impacts of technological change and Measurement of scientific and technological activity as from indicators , this work purposes to observe the question of scientific periodical publications, mainly the electronic scientific periodical, for guise of these two questions, through the analysis of Revista de Letras, institutional periodical from São Paulo State University, that combine several elements that enable the fulfillment of purpose. We objectify with this study attend for what challenges and factors propel the change for electronic form , the impact of co-existence of periodical in its printed and electronic form, beyond provide one characterization of its scientific production for critical and literary production area on the eve of its 50 years and then demonstrate the importance of multidisciplinary and critical view of STS field in question of electronic scientific periodicals.